Gene therapy of locally advanced vulvar cancer with psFLT construct - Gawrychowski, Krzysztof; Małecki, Maciej; Szewczyk, Grzegorz; Panek, Grzegorz; Śmiertka, Wacław; Roszkowska-Purska, Katarzyna; Bidziński, Mariusz; Sadowska, Małgorzata; Surowińska, Joanna; Dąbrowska, Monika; Górniak, Anna; Krynicki, Ryszard; et al. (Contemporary Oncology/Współczesna Onkologia, 2010)
Introduction: An interesting strategy in experimental therapy of neoplasms is genetic-based antiangiogenic therapy. The basis for this therapy is the premise that development of new tumour vessels is a direct factor for tumour growth. The psFLT construct is a plasmid expression vector that encodes the antiangiogenic factor. It consists of a gene fragment of the VEGF receptor Flt which encodes the soluble form of this receptor. The aim of the study was to assess the response to treatment in patients with vulvar cancer after local administration of psFLT construct. Material and methods: 21 patients with vulvar cancer (1B-4A stage according to FIGO) were recruited into the study. Patients were given a local injection of 800 mg psFTL-1 construct dose (0.4 mg/ml). 6-10 injections were made in the tumour vicinity (1-2 cm) and the treatment was repeated after 2 weeks. In the assessment of the therapy the total area of the tumour and the relative change in the area (compared to the primary area) were measured after 3-6 weeks from the first treatment. Results: The response to treatment defined as above was achieved in 16 patients with good tolerance of the treatment. Surgical treatment was performed in 13 patients after administration of the construct and in 4 patients only radio-chemotherapy was performed. Marginal necrosis was observed in 12 patients after the following surgery treatment in histopathological examination with the maximum reaching 40% of the tumour volume. Significant differences in tumour area change were observed after administration of the 1st dose of the construct as well as after the 2nd dose. It seems that use of psFLT construct in locally advanced vulvar cancer can give real advantages for patients due to reducing local cancer infiltration and improving quality of life.